Collaborative Strategy for Teaching and Learning Object-Oriented Programming course: A Case Study at Mostafa Stambouli Mascara University, Algeria - Boudia, Cherifa; Bengueddach, Asmaa; Haffaf, Hafid (Informatica, 2019)
Several strategies and methods have been designed and tested to allow students to have better teaching and learning of programming concepts and training their programming skills acquired. In our university, old and classic pedagogical methods are still used in the learning of Oriented-Object Programming (OOP). This paper explores the experimentation of a pedagogical approach designed for Mostafa Stambouli Mascara University’s computer sciences students to enhance their chances to get an effective teaching using a collaborative learning and early introduction of current technologies. The study was made of 108 second year informatics students’ for two semesters (October–January 2016-2017, September-December 2017-2018) who were identified in a controlled experience for collaborative learning OOP in lab session. Students gathered into predetermined groups based on initial test and some settings. The students are supposed to share the same programming assignment by distributing roles according to global pedagogical scenario for problem-resolving activities. This experience allows the teachers to apply this strategy and see students in closer and permit them to express their problems and search together for solutions. The principal objective was to offer a new experience to motivate students and make this design a smart opportunity to have better programming performance. Furthermore, as a result of testing this new strategy, the students’ academic progress is clear. A questionnaire was distributed with the purpose of analyzing students’ motivation and satisfaction levels alongside the effects of the experiment. Results show that students found that among other benefits this method facilitates the learning process.